Laboratory System for Intensive Cultivation of Microalgae and Cyanobacteria - Gabrielyan, D. A.; Sinetova, M. A.; Gabrielyan, A. K.; Bobrovnikova, L. A.; Bedbenov, V. S.; Starikov, A. Yu; Zorina, A. A.; Gabel, B. V.; Los, D. A. (Russian journal of plant physiology, 2023)
Currently, microalgae and cyanobacteria attract the attention of researchers as potential producers of various valuable substances. To increase the profitability of biotechnological processes using these organisms, it is necessary to select highly effective strains and choose the optimal conditions for their growth and maximum productivity. Growth optimization should be carried out, on the one hand, under intensive conditions, as close as possible to large-scale cultivation, and, on the other hand, in small volumes in order to be able to check many different parameters in parallel at minimal cost. In this paper, the authors present a description and characteristics of their laboratory system for intensive cultivation (LSIC—Laboratory System for Intensive Cultivation) with thermo-, light-, and gas regulation and the possibility of cultivation in four repetitions in eight different conditions, differing in light, temperature, and CO 2 concentration. As an example, the results of a number of experiments using the installation are also presented.